Some Characterizations of General Preinvex Functions - Muhammad Uzair Awan; Muhammad Aslam Noor; Vishnu Narayan Mishra; Khalida Inayat Noor (International Journal of Analysis and Applications, 2017)
In this paper, we consider a new class of general preinvex functions involving an arbitrary function. We show that the optimality condition for general preinvex functions on general invex set can be characterized by a class of variational-like inequality. We also derive some integral inequalities of Hermite-Hadamard type via general preinvex functions. Some special cases are also discussed. Our results represent a significant refinement of the previously known results. These results may stimulate further research in this area.